Cross-Border M&A Flows, Economic Growth, and Foreign Exchange Rates - Riddiough, Steven J; Zhang, Huizhong (Review of Financial Studies, 2025)
Abstract We extract information about future economic conditions from firms’ cross-border merger and acquisition announcements, and show it predicts changes in relative economic growth rates and foreign exchange rate returns. We find the predictability is driven by the acquisition decisions of domestic firms, which signal turning points in local economic growth. The findings are motivated by a simple model of exchange rate determination with heterogeneous expectations and support the theorized relationship between foreign exchange rates and macroeconomic fundamentals. The results provide new tools for policy makers seeking to predict economic activity and offer global investors a novel source of portfolio diversification.